SilverComm: Marketing Practices and Messages for the Age of Aging - Liu, Yi (COMUNICACIÓN. Revista Internacional de Comunicación Audiovisual, Publicidad y Estudios Culturales, 2024)
Reseña de SilverComm: Marketing Practices and Messages for the Age of Aging (Anne M. Cooper & Young-Joon Lim, 2023).